PEMIKIRAN K.H. A. WAHID HASYIM TENTANG EPISTEMOLOGI KOMPONEN PENDIDIKAN, DAN IMPLIKASINYA DALAM PENDIDIKAN - Zuhri Zuhri (Jurnal Studi Islam dan Sosial, 2019)
This research has a problem statement, namely; 1). How is the socio-historical K.H.wahid Hasyim? 2). How does K.H.Wahid Hasyim think about the epistemology of educational components ?. 3). How is K.H.Wahid Hasyim's thoughts and implications in education now? This research has a purpose, namely; 1) .to explain the socio-historical K.H.Wahid Hasyim. 2). To explain about K.H's thinking Wahid Hasyim on the Epistemology of Education Components. 3). To explain about the thinking of K.H.Wahid Hasyim and its implications in education now. This study aims to realize education in accordance with the concept of Islamic education, which is to increase devotion, and aims to create noble character, as well as educational outcomes to realize human beings who can answer the challenges of changing times, to answer that by reading the history of his biography and his thoughts on Islamic education, as research object. Research conclusions, namely; 1). K.H. wahid Hasyim, born, educated, guided and raised in the boarding school environment, by his father K.H. Hasyim Ash'ari, with the main foundation of learning the Koran and other classical books; Fatkhul Qorib, Minhajul Qowim, and raised directly by his father. And like adventure learning in various other boarding schools, age 12 years have graduated at Tasfiyah Madrasah, at the age of 15 began to get to know other general sciences. 2). Movement of thought about education, among others; a). Students are pure white people who must be filled with various scientific knowledge to respond to the basic potential that exists. b). The purpose of his education is to increase his devotion and noble character, and various knowledge in order to be able to answer the challenges of the times, and the problems of society, for worldly and ukhrawi good. c). The bandongan learning method is considered to educate passive students, then it is replaced by a method that evokes students' active responses, and does not adhere to just one method, d). pandidik, is a person who is really diligent and focused and attentive in totality, and students are recognized by their own children, not other people's children. e). About the curriculum, according to him, it covers religious knowledge as a form of piety and personality, science as a provision of life skills. 4). K.H.Wahid Hasyim's thoughts are relevant to the dynamics of education, so it is very appropriate to be applied in Islamic boarding schools, madrasas and higher education.